Management of Chemotherapy and Radiotherapy-Induced Side Effects in Pancreatic Carcinoma Through Panchagvya and Other Shamana Chikitsa in Ayurveda - A Case Report: Life Sciences -Ayurveda - Sawarkar, Dr. Gaurav; Sawarkar, Dr. Punam (International Journal of Life Science and Pharma Research, 2023)
Pancreatic cancer is a carcinoma with a poor prognosis due to a high mortality rate. There are 10 cases in the 1,00,000 population per annum. Surgical intervention, Chemo & radiotherapy are the conventional measures to treat these conditions. However, due to the specific side effects of Chemo & radiotherapy, search strategies for the Safest Ayurvedic intervention are highly needed. The prime aim of this paper is to study the efficacy of Ayurvedic treatment in managing the side effects of Chemotherapy in pancreatic Carcinoma of a male patient. In a single case study, a patient diagnosed with CA Pancrease was advised for Chemo-Radiation therapy. However, the severity of the complaints, such as Anorexia, nausea, vomiting, and epigastric pain, worsened after one of Chemotherapy & remained throughout the day. Despite taking the antacid suggested by the oncologist, there was no relief in symptoms. Therefore, a patient approached Ayurvedic Chikitsa. Shamana Ayurvedic Chikitsa (Praval Pishti, Gulvel Satva, Suvarna Sootshekhar Rasa, Moutikta Kamdudha & Chandrakala Rasa) for six consecutive monthswas prescribed. After 3-5 days, the patient has observed significant relief in the above symptoms & he was able to take his regular diet. The frequency of vomiting was also reduced significantly. After six months of standard treatment, his weight also improved. Three sittings of Chemo & radiotherapy were completed without any hurdles & no associated side effects. The selected combination of all Ayurvedic medicines induces relief in symptoms due to their Agnidipak, Vata-Pitta Shamak Chhardighna, Yakrutotejjak&Rasayana properties. In the present case report, the above said Ayurvedic prescription significantly induces relief in side-effects of Chemo & radiotherapy due to its Pitta Shamak&Agnivardhaka effects.